2010
DOI: 10.3758/s13421-010-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of landmark and body-based sensory information on route knowledge

Abstract: Two experiments investigated the effects of landmarks and body-based information on route knowledge. Participants made four out-and-back journeys along a route, guided only on the first outward trip and with feedback every time an error was made. Experiment 1 used 3-D virtual environments (VEs) with a desktop monitor display, and participants were provided with no supplementary landmarks, only global landmarks, only local landmarks, or both global and local landmarks. Local landmarks significantly reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 34 publications
(52 reference statements)
5
85
2
Order By: Relevance
“…The addition of motor, proprioceptive, and possibly vestibular information due to walking during exploration appears to improve performance on survey tasks such as pointing, over and above passive vision alone Waller et al, 2004). Similar results are also seen in route learning and wayfinding tasks Ruddle et al, 2011a;Ruddle et al, 2011b). This pattern seems to hold especially with complex paths or repeated exposure to the same environment Waller & Greenauer, 2007), suggesting that passive vision may be sufficient for simple environments (Mellet et al, 2010) and that idiothetic learning may build up over time.…”
Section: Idiothetic Information During Walkingmentioning
confidence: 55%
See 2 more Smart Citations
“…The addition of motor, proprioceptive, and possibly vestibular information due to walking during exploration appears to improve performance on survey tasks such as pointing, over and above passive vision alone Waller et al, 2004). Similar results are also seen in route learning and wayfinding tasks Ruddle et al, 2011a;Ruddle et al, 2011b). This pattern seems to hold especially with complex paths or repeated exposure to the same environment Waller & Greenauer, 2007), suggesting that passive vision may be sufficient for simple environments (Mellet et al, 2010) and that idiothetic learning may build up over time.…”
Section: Idiothetic Information During Walkingmentioning
confidence: 55%
“…They found that the addition of physical translation aided learning only by leading to less total distance traveled during search. Ruddle, Volkova, Mohler, and Bülthoff (2011b) examined body-based contributions to route knowledge. They had some participants walk in a virtual environment to follow a specified route and then asked them to retrace the route and repeat the out-and-back route several times.…”
Section: Idiothetic Information During Walkingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Experiment 2 of [Ruddle, Volkova, Mohler and Bülthoff 2011], the HMDwalk group made significantly fewer errors than the HMD turn group and some of that difference may be attributed to a difference between the groups' interface proficiency. However, interface proficiency does not account for the marked advantage that the HMDwalk group showed on the return legs of the route, compared with the outward legs.…”
Section: Discussionmentioning
confidence: 87%
“…We assessed the percentage errors and the mean angular errors. These direction estimates are expected to be accurate when participants have memorized a well-developed, map-like representation of the environment [10]. This task measures survey knowledge.…”
Section: Restitution Phasementioning
confidence: 99%